Sobre conocimiento y significado en el Essay de John Locke - Burlando, Giannina (Veritas, 2013)
At the very end of Book II of ‘An Essay Concerning Human Understanding’, Locke finds out «that there is so close a connexion between Ideas and Words […] that it is impossible to speak clearly and distinctly of our Knowledge, which all consists in Propositions, without considering first the Nature, Use, and Signification of Language». In various and diverse ways Locke defends the thesis that ‘Words signify Ideas’. My aim in this paper is first, to sum up Locke’s general theory of Language; secondly, to revisit some regular objections concerning this theory, and thirdly, to intend an explanation of what Locke means when he points out that ‘Words signify ideas’. In regard to this point, I shall hold up E. J. Ashworth’s interpretation to show that Locke semantic thesis involves the use of the verb ‘to signify’ (‘signifying’) not in the manner that it is used by contemporary theorists of the twentieth century, but in the sense that some scholastics used the term ‘significare’.